The Injuries from Artistic Gymnastics Training of Athletes Who Participated in the 39th National Sport Competition Chonburi Province, Thailand - Rattanakaew, Jitraporn; Prajunban, Sathin (Academic Journal of Thailand National Sports University, 2022)
The purpose of this study was to study the injuries of athletes training to compete in artistic gymnastics in The 39th National Sport Competition, Chonburi Province, Thailand, The sample consisted of 43 artistic gymnasts classified into 13 male athletes and 30 female athletes drawn by purposive sampling. The instrument used in this research was a questionnaire concerning with the injured athletes from training. Its reliability was 91. The data were analyzed by frequency and percentage. The research results were as follows: The state of respondents of injured athletes were found that 67.77% from most of the female athletes and 30.23% from most of the male athletes respectively. The aspect of playing artistic gymnastics experience was found that 84.62% from most of the male athletes who had the experience of playing artistic gymnastics over 5 years, followed by 4-5 years were at 84.62% and 15.38% respectively. In alternative most of the female athletes who had the experience of playing artistic gymnastics over 5 years, followed by 4-5 years were at 83.33% and 16.67% respectively. The aspect of artistic gymnastics competition experience was found that most of the male athletes who had the experience of artistic gymnastics competition 5 times up, followed by most of the female athletes were at 100% and 86.87%. The cause of artistic gymnasts' injuries: From extrinsic environment was found that most of the male athletes who injured from clashing with barriers and the other trainees, followed by from old damaged equipments and not up to standard were at 53.84% and 38.46% respectively. Most of the female athletes who injured from clashing with barriers and the other trainees, followed by from too high and too low temperature were at 56.67% and 40% respectively. From the athletes themselves was found that the aspect of body, most of the male athletes who injured from lacking of warming up enough and lacking of techniques in training, followed by from the fatigue were at 53.84% and 38.46% respectively. Most of the female athletes who injured from lacking of warming up enough and lacking of techniques in training, followed by from the fatigue were at 66.67% and 36.67% respectively. From the mental was found that most of the male athletes who injured from the anxiety, followed by from the stress were at 69.23% and 61.54% respectively. Most of the female athletes who injured from the anxiety and lacking of concentration were at 46.67% and 43.33% respectively. The injured body parts: At upper external organs was found that most of the male athletes who injured at the shoulder, followed by at lower back were at 61.53% and 38.46% respectively. Most of the female athletes who injured at the shoulder and fingers, followed by at lower back were at 61.53% and 38.46% respectively. At lower s was found that most of the male athletes who injured at the knee, followed by the ankle were at 69.23% and 53.84% respectively. Most of the female athletes who injured at the ankle, followed by the knee were at 63.33% and 33.33% respectively. The characteristic of injuries: At the skin was found that most of the maleathletes who injured at torn palms, followed by bruised skin were at 76.92% and 38.46% respectively. Most of the female athletes who injured at torn palms, followed by bruised skin were at 66.67% and 46.67% respectively. At the muscle was found that most of the male athletes who injured at the symptom of painful muscle, followed by cramps were 92.30% and 23% respectively. Most of the female athletes who injured at the symptom of painful muscle, followed by sprains were at 70% and 53.33% respectively. Gymnastic equipments that can cause injuries was found that most of the male athletes who injured from the horizontal bar, followed by the floor exercise were at 81.10% and 75.10% respectively. Most of the female athletes who injured from the uneven bar, followed by the vaulting horse were at 80.12% and 73.33% respectively. The symptoms of injuries was found that the severe level of the symptoms of most of the male athletes were not serious, 61.53% of them were still able to do the practice on the next day, followed by 30.77% of them were so serious that they had to see formal medical doctors to diagnose and cure respectively. The severe level of the symptoms of most of the female athletes were not serious, 70% of them were still able to do the practice on the next day, followed by 16.67% of them were so serious that they had to stop the movement and were unable to do the practice on the next day but no need to receive treatments from formal medical doctors respectively. First aid after being injured from training during in 24 hours was found that most of the male athletes, 100% used applying a compress with ice, followed by 46.15% used applying or taking medicine for releasing pain respectively. The aspect of the rehabilitation treatment was found that most of the male athletes, 61.54% received treatments from physiotherapist, followed by 53.82% received treatments from their coaches respectively. The duration of the treatment rehabilitation was found that most of the male athletes at 53.84% spent less than one week, followed by 23.07% spent 1-2 weeks for curing their injuries respectively. Most of the female athletes at 90% used applying a compress with ice, followed by 80% used applying or taking medicine for releasing pain respectively. The aspect of the rehabilitation treatment was found that most of the female athletes, 63.33% received treatments from their coaches, followed 56.67% received treatments from formal medical doctors respectively. The duration of the treatment rehabilitation was found that most of the female athletes at 56.67% spent less than one week, followed by 26.67% spent 1-2 weeks for curing their injuries respectively.